Lymphatic Patterns in the Superficial Circumflex Iliac Artery Perforator Flap - Campos, José Luis; Suominen, Sinikka; Pons, Gemma; Al-Sakkaf, Ali M.; Lusetti, Irene Laura; Sirota, Max; Vela, Francisco Javier; Pires, Laura; Sánchez-Margallo, Francisco Miguel; Abellán, Elena; Masiá, Jaume (Journal of Reconstructive Microsurgery, 2024)
Background Lymphedema is a chronic condition, characterized by fluid buildup and tissue swelling and is caused by impairment of the lymphatic system. The lymph interpositional flap transfer technique, in which lymph flow is restored with a flap that includes subdermal lymphatic channels, is an option for surgical reconstruction. The superficial circumflex iliac artery perforator (SCIP) flap can be used for this purpose. This study aimed to describe and characterize the lymphatic patterns within the vascular territory of the SCIP flap.Methods This cross-sectional multicenter study involved 19 healthy volunteers aged ≥18 years of both sexes assessing the bilateral SCIP flap zone. Superficial lymphatic patterns were evaluated at 4-, 14-, and 24 minutes after indocyanine green (ICG) lymphography injection. Standardized procedures were implemented for all participants in both hospitals.Results The linear pattern was predominant bilaterally. The median number of lymphatic vessels and their length increased over time. Most lymphatic vessels in the SCIP flap were oriented toward the inguinal lymph node (ILN). However, the left SCIP zone lymphatic vessels were directed opposite to the ILN.Conclusion The two sides SCIP zones were not significantly different. The primary direction of the bilateral lymphatic vessels was toward the ILN, although only single-side lymphatic vessels were in the opposite direction. These findings emphasize the importance of assessing lymphatic axiality and coherent lymphatic patterns prior to undertaking the SCIP as an interposition flap, to ensure effective restoration of lymphatic flow.
Keywords: lymph; lymphedema; microsurgery; SCIP flap; lymphatic pattern